Quantitative determination of cefepime in plasma and vitreous fluid by high-performance liquid chromatography - Valassis, IN; Parissi-Poulou, M; Macheras, P. (JOURNAL OF CHROMATOGRAPHY B, 1999)
An isocratic reversed-phase HPLC method was developed to determine cefepime levels in plasma and vitreous fluid. Cefepime and the internal standard cefadroxil were separated on a Shandon Hypersil BDS C18 column by using a mobile phase of 25 mM sodium dihydrogen phosphate monohydrate (pH 3) and methanol (87:13, v/v). Ultraviolet detection was carried out at 270 nm. The retention times were 4.80 min for cefepime and 7.70 min for cefadroxil. This fast procedure which involves an efficient protein precipitation step (addition of HClO4), allows a quantification limit of 2.52 mu g ml(-1) and a detection limit of 0.83 mu g ml(-1). Recoveries and absolute recoveries of cefepime from plasma were 96.13-99.44% and 94-102.5% respectively. The intra-day and inter-day reproducibilities were less than 2% for cefepime at 10, 30, 50 mu g ml(-1) (n=10). The method was proved to be suitable for determining cefepime levels in human plasma and was modified to measure vitreous fluid samples. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: cefepime; plasma; vitreous fluid